Risk factors and outcome of hepatitis C infection among patients in a secondary care hospital: A 5-year retrospective study - Mohan B. Sannathimmappa; Latifa Zehri; Ayat A. M. Al Zadjali; Halima M. A. Albalushi; Buthaina A. A. H. Al Saadi; Rajeev Aravindakshan; Elham S. Al-Risi; Saleema Al-Maqbali; Vinod Nambiar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Hepatitis C virus (HCV) infection, predominantly transmitted by exposure to infected blood, remains one of the major public health problems worldwide. This study aims to identify the risk factors of HCV transmission and its chronic complications among the study group. MATERIALS AND METHODS: This retrospective study was approved by the Research and Ethical Review and Approve Committee (RERAC) of Oman and conducted at a secondary-care hospital situated in the North Batinah region of Oman. The study population included all HCV cases confirmed by positive serology and reverse-transcription polymerase chain reaction tests during their presence at the hospital between January 2017 and December 2022. The relevant data of the study population were retrieved from the hospital electronic health record system. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), Version 26.0. RESULTS: A total of 177 HCV confirmed cases were included in the study. HCV infection was predominant among males (74%) and individuals of the age group of 21-60 years (74.6%). Genotyping was possible only in 107 cases. Among HCV genotypes, genotype 3 (58.9%) was the most frequently identified, followed by genotype 1 (34.6%). Hemodialysis (21.5%), history of blood transfusion (16.4%), and injection drug use (11.9%) were the major risk factors for HCV infection, while cirrhosis (7.3%) and fatty liver disease (4%) were the most frequently observed chronic HCV complications. HCV infection in the spouse/partner (21.5%), alcohol use (7.3%), and co-infection with hepatitis B virus (2.3%) and human immunodeficiency virus (1.7%) were the other significant factors detected in our study population. CONCLUSIONS: HCV is a multi-factorial disease leading to severe chronic complications, thus representing a public health threat. This clearly emphasizes the cruciality of HCV community awareness campaigns and enhancement of Omani national guidelines for early screening of high-risk groups as well as effective management of HCV-infected cases to reduce the substantial burden of the disease on patients as well as the healthcare system.